COMPUTERIZED MEDICAL RECORD ON HOSPITAL XYZ - Eka Kurniawati; Drs. Eko Hadiyanto, MM (Jurnal Sistem Informasi, 1997)
A system can be said to be good, if such information or can provide a certain report to the needy is a good and timely. From the analysis of the current system, particularly the Medical Records Inpatient and Outpatient there are some constraints such as the slow process of borrowing the file. Therefore, in order to facilitate the borrowing of these files by creating better systems and computerized.